Comparative Safety Signal Assessment of Hospitalization Associated With the Use of Atypical Antipsychotics - Yunusa, Ismaeel; Teng, Chengwen; Karaye, Ibraheem M.; Crounse, Emily; Alsahali, Saud; Maleki, Nasim (Frontiers in Psychiatry, 2022)
Background Persons with symptoms of psychosis receiving treatment with atypical antipsychotics (AAPs) can experience serious adverse events (AEs) requiring admission to the hospital. The comparative likelihood of AE-related hospitalization following the use of all AAPs has not been fully characterized. Therefore, we evaluated the safety signals of hospitalizations associated with the use of AAPs. Methods We conducted a cross-sectional analysis using the FDA Adverse Event Reporting System (FAERS) database (from January 1, 2004, to December 31, 2021) to examine disproportionality in reporting hospitalizations suspected to be associated with 12 AAPs (aripiprazole, asenapine, brexpiprazole, clozapine, iloperidone, lurasidone, olanzapine, paliperidone, and pimavanserin, quetiapine, risperidone, and ziprasidone). Hospitalization in the FAERs database is an outcome that is recorded as a result of an AE occurring at any drug dose. We estimated reporting odds ratios (RORs) by comparing the odds of hospitalization occurring with a particular AAP to the odds of its occurrence with other drugs. In addition, we considered the presence of a significant safety signal when the lower limit of the 95% confidence interval (CI) of the ROR is >1. Results A total of 204,287 cases of hospitalizations were reported to the FDA for individuals treated with AAPs. There were significant safety signals of hospitalization associated with using clozapine (ROR, 2.88; 95% CI, 2.84–2.92), olanzapine (ROR, 2.61; 95% CI, 2.57–2.64), quetiapine (ROR, 1.87; 95% CI, 1.85–1.89), risperidone (ROR, 1.41; 95% CI, 1.39–1.43), aripiprazole (ROR, 1.34; 95% CI, 1.32–1.35), and ziprasidone (ROR, 1.14; 95% CI, 1.10–1.18). However, no hospitalization-related safety signals were observed with the use of paliperidone, pimavanserin, iloperidone, asenapine, lurasidone, and brexpiprazole. The ROR estimates were numerically higher among older adults than younger adults. Conclusions This cross-sectional assessment of data from FAERs (2004–2021) suggested that users of clozapine, olanzapine, quetiapine, risperidone, aripiprazole, and ziprasidone were more likely to report being hospitalized than users of other AAPs. Given that the FAERs database only contains spontaneous reports of AEs experienced by persons exposed to a drug but without information on exposed persons who did not have an event, a cohort study comparing hospitalizations among new users of individual AAPs against each other is needed to delineate these safety signals further.